Effects of thymidine and uridine on the phosphorylation of 3'-azido-3'-deoxythymidine (zidovudine) in human mononuclear cells. - Szebeni, J (1991)
The effects of thymidine and uridine on the phosphorylation of 3'-azido-3'-deoxythymidine (AZT) were studied in various human mononuclear cell preparations. Thymidine suppressed [3H]AZT phosphorylation in the same concentration range (20 to 100 microM) in which it antagonizes the anti-human immunodeficiency virus activity of AZT. Uridine, in turn, had no influence on AZT phosphorylation, just as it has no effect on the anti-human immunodeficiency virus activity of AZT. These findings are consistent with a close relationship between the inhibition of AZT phosphorylation and the influence of physiological nucleosides on the antiviral activity of AZT.